Actomyosin bundles serve as a tension sensor and a platform for ERK activation. (30th December 2014) - Hirata, Hiroaki; Gupta, Mukund; Vedula, Sri Ram Krishna; Lim, Chwee Teck; Ladoux, Benoit; Sokabe, Masahiro
Abstract Tensile forces generated by stress fibers drive signal transduction events at focal adhesions. Here, we report that stress fibers per se act as a platform for tension‐induced activation of biochemical signals. The MAP kinase, ERK is activated on stress fibers in a myosin II‐dependent manner. In myosin II‐inhibited cells, uniaxial stretching of cell adhesion substrates restores ERK activation on stress fibers. By quantifying myosin II‐ or mechanical stretch‐mediated tensile forces in individual stress fibers, we show that ERK activation on stress fibers correlates positively with tensile forces acting on the fibers, indicating stress fibers as a tension sensor in ERK activation. Myosin II‐dependent ERK activation is also observed on actomyosin bundles connecting E‐cadherin clusters, thus suggesting that actomyosin bundles, in general, work as a platform for tension‐dependent ERK activation.